Sleep architecture modifications after double chronotherapy: A case series of bipolar depressed inpatients. (October 2022) - Sarzetto, Alessandro; Cavallini, Maria Cristina; Fregna, Lorenzo; Pacchioni, Federico; Attanasio, Francesco; Barbini, Barbara; Franchini, Linda; Colombo, Cristina
Highlights: Total sleep deprivation combined with light therapy is a powerful treatment for bipolar depression. The effect of chronoterapeutics on sleep has never been objectively assessed, despite the well-known importance of sleep in bipolar disorder. Sleep architecture modifications were observed after treatment with double chronotherapy, especially regarding sleep stages 2 and 3, and REM density. Reduction of N3 sleep was correlated with depressive symptoms reduction. Abstract: The aim of this study is to objectively evaluate sleep architecture changes of depressed bipolar subjects treated with chronoterapeutics. Eleven depressed bipolar inpatients received 3 cycles of Total Sleep Deprivation, followed by daily light therapy sessions for one week. Polysomnography was performed before and after the treatment. Depressive symptoms significantly reduced, and sleep architecture changed with significant differences in N2% and N3% and REM density. Change in N3% was also positively correlated to depressive symptoms reduction. Although, previous studies reported sleep architecture changes after chronoterapeutics in unipolar depression, this is the first study to demonstrate changes also in bipolar depressed subjects.